2019
DOI: 10.1186/s12889-019-6867-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral health-related quality of life and nutritional status among older adults in district of Kuala Pilah, Malaysia

Abstract: Background Poor oral health has an impact on food choices and intake of important nutrients among older population. The use of oral health-related quality of life instruments along with the clinical dental indicators can help to assess the oral problems that lead to nutritional problems in this group. This study aims to determine the association between oral health-related quality of life (OHRQoL) and nutritional status among a group of older adults in Kuala Pilah district, Malaysia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 30 publications
4
33
0
7
Order By: Relevance
“…Fifth, a similar approach for investigating psychiatric patients' OHRQoL was used in French study [26]. Finally, other factors, such as chewing function [22], nutritional status [24], and cognitive function status [25], might be associated with OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, a similar approach for investigating psychiatric patients' OHRQoL was used in French study [26]. Finally, other factors, such as chewing function [22], nutritional status [24], and cognitive function status [25], might be associated with OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…The GOHAI can be self-administered and is quick and easy to use. Several studies have reported that age, number of remaining teeth, regular dental check-ups, chewing function, and cognitive function were associated with GOHAI [20][21][22][23][24][25]. However, there are few studies regarding psychiatric patients' OHRQoL [26,27] and no studies regarding the associations between age, OHRQoL, and oral health, including oral and swallowing function, among psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Forth, a similar approach for investigating psychiatric patients' OHRQoL was used in French study [26]. Finally, other factors, such as chewing function [22], nutritional status [24], and cognitive function status [25], might be associated with OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…The GOHAI can be selfadministered and is quick and easy to use. Several studies have reported that age, number of remaining teeth, regular dental check-ups, chewing function, and cognitive function were associated with GOHAI [20][21][22][23][24][25]. However, there are few studies regarding psychiatric patients' OHRQoL [26,27] and no studies regarding the associations between age, OHRQoL, and oral health, including oral and swallowing function, among psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Research in the region [2], Europe [3,4,5] and other continents [6][7][8][9] has influenced the launch of research on the oral health status of the elderly in Montenegro. Studies of the impact of oral health on the quality of life have been conducted worldwide for more than five decades and a high degree of interdependence between quality of life and oral health has been proven [10][11][12][13][14]. These findings have been implemented in a new definition of oral health [15,16].…”
Section: Introductionmentioning
confidence: 99%